The Effect of Fermented Tofu Dregs Using EM4 Probiotics on Population Growth of Daphnia Magna - Safitri, Mardiani; Pamukas, Niken Ayu; Rumondang, Anne; Pamukas, Nike Ayu (Jurnal Media Akuakultur Indonesia, 2023)
Daphnia magna is a small crustacean or often called a water flea that lives in fresh waters. According to Putri et al., (2015), the nutritional content of Daphnia magna is 39.24% protein, 4.98% fat, 4.32% carbohydrates, ash content 14.63%. One of the Daphnia magna foods that can be given is tofu pulp which has a protein content of 27.55% to support its growth. The aim of this research was to obtain the most optimal growth of Daphnia magna after being given fermented tofu dregs at different doses. The method used was an experiment with a completely randomized design consisting of 4 treatments and 3 replications. The treatment carried out consisted of giving fermented tofu dregs in Daphnia magna maintenance media with different doses, namely P0 (0 gr/control), P1 (20 gr), P2 (30 gr), P3 (40 gr). Based on the results of research that has been carried out, it was found that P2 treatment with a dose of 30 grams gave the highest growth of Daphnia magna at 1,460 individuals. The high number of Daphnia magna populations given a dose of 30 grams can be utilized optimally for the growth and survival of Daphnia magna. The research results obtained concluded that giving fermented tofu dregs at a dose of 30 gr (P2) was able to have a significant effect (P < 0.05) on the increase in the Daphnia magna population.